On the Potential of Phase-change Adsorbents for CO2 Capture by Temperature Swing Adsorption. (July 2017) - Joss, Lisa; Hefti, Max; Bjelobrk, Zoran; Mazzotti, Marco
Abstract: The objective of this work is to assess the potential of a novel class of metal organic framework (MOF) materials recently introduced [McDonald et al., Nature, 2015, 519, 303] for post-combustion CO2 capture by temperature swing adsorption (TSA). In particular, we present figures for the process performance obtained from optimizing operating conditions of a four-step TSA cycle. Our results show that high purity and high recovery can be attained. Subsequently, we benchmark the performance in terms of energy consumption and productivity to a state-of-the-art TSA process using zeolite 13X [Joss. et al. Chem. Eng. Sci. under review]. While the energy consumption is similar, a higher productivity can be obtained using these MOF materials. Finally, we make a comparison to amine-scrubbing processes and show that, after applying heat integration, similar performance can be expected.